2012
DOI: 10.1056/nejmoa1200501
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Agents and Prevention of Malaria in HIV-Infected Ugandan Children

Abstract: Background Human immunodeficiency virus (HIV) protease inhibitors show activity against Plasmodium falciparum in vitro. We hypothesized that the incidence of malaria in HIV-infected children would be lower among children receiving lopinavir–ritonavir–based antiretroviral therapy (ART) than among those receiving nonnucleoside reverse-transcriptase inhibitor (NNRTI)–based ART. Methods We conducted an open-label trial in which HIV-infected children 2 months to 5 years of age who were eligible for ART or were cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
125
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 97 publications
(132 citation statements)
references
References 19 publications
5
125
2
Order By: Relevance
“…The details of these studies have been previously published. [6][7][8] These samples were selected randomly for our study after stratifying based on parasite density, which was determined by thick smear.…”
Section: Methodsmentioning
confidence: 99%
“…The details of these studies have been previously published. [6][7][8] These samples were selected randomly for our study after stratifying based on parasite density, which was determined by thick smear.…”
Section: Methodsmentioning
confidence: 99%
“…9 In this study the use of PI-based ART was associated with a 41% reduction in the incidence of malaria, largely attributable to ART-antimalarial drug interactions resulting in a significant reduction in the risk of recurrent malaria after treatment with artemether-lumefantrine (AL). In this report, we compare the prevalence of asymptomatic parasitemia and gametocytemia between ART treatment arms in this trial.…”
mentioning
confidence: 96%
“…9 Specifically, the ritonavir component of the PI regimen inhibited the metabolism of lumefantrine, leading to prolongation of exposure to lumefantrine, and thus prolonged protection against recurrent malaria after treatment. To explore whether prolonged lumefantrine exposure after treatment also contributed to the lower risk of gametocytemia on the day malaria was diagnosed in the PI-based arm, results were stratified by duration since the last episode of malaria (Figure 1).…”
mentioning
confidence: 99%
“…There is early evidence that antiretroviral therapy (ART) may reduce malaria in HIV-infected persons. 68 Because HIV and malaria endemicity overlap globally, and the overwhelming burden of HIV-malaria co-infection is found in sub-Saharan Africa, 11 RDTs could make an enormous impact. Presumptive treatment of fevers in HIV-positive persons with malaria drugs is extremely common, but laboratory confirmation of malaria infection is not uniformly conducted.…”
Section: Rapid Diagnostic Testsmentioning
confidence: 99%
“…48 Although evidence supports a higher incidence of clinical malaria and severe malaria in HIV-infected children, recent studies have also reported a reduction in malaria rates in HIV-infected persons receiving trimethoprim-sulfamethoxazole prophylaxis, as well as reports of reduced rates of malaria for those children receiving certain ART regimens. 11,68 Thus, the selected diagnostic modality must be carefully monitored to ensure its continued effectiveness in the setting of this complex and evolving interaction.…”
Section: Rapid Diagnostic Testsmentioning
confidence: 99%